Genetic Privacy, Disease Prevention, and the Principle of Rescue - Kilbride, Madison K. (The Hastings Center report, 2018)
Suppose that you have deeply personal information that you do not want to share. Further suppose that this information could help others, perhaps even saving their lives. Should you reveal the information or keep it secret? With the increasing prevalence of genetic testing, more and more people are finding themselves in this situation. Although a patient's genetic results are potentially relevant to all her biological family members, her first-degree relatives—parents, children, and full siblings—are most likely to be affected. This is especially true for genetic mutations—like those in the BRCA1 and BRCA2 genes—that are associated with a dramatically increased risk of disease. Fortunately, people are usually willing to share results with their at-risk relatives. Occasionally, however, a patient refuses to disclose her findings to anyone outside her clinical team. Ethicists have written little on patients’ moral duties to their at-risk relatives. Moreover, the few accounts that have been advanced are problematic. Some unnecessarily expose patients’ genetic information to relatives who are unlikely to benefit from it, and others fail to ensure that patients’ most vulnerable relatives are informed of their genetic risks. Patients’ duty to warn can be defended in a way that avoids these problems. I argue that the duty to share one's genetic results is grounded in the principle of rescue—the idea that one ought to prevent, reduce, or mitigate the risk of harm to another person when the expected harm is serious and the cost or risk to oneself is sufficiently moderate. When these two criteria are satisfied, a patient will most likely have a duty to warn.